Modified Crossed-Wire Antennas Radiating a Circularly Polarized Conical Beam - Hirose, Kazuhide; Nakano, Hisamatsu; Hata, Kazuhiko (International journal of antennas and propagation, 2020)
Two types of modified crossed-wire antennas are investigated to enhance a circularly polarized (CP) wave bandwidth. The wire length of each antenna is increased twice as long as that of the original antenna. First, a bent-type antenna is analyzed using the method of moments. It is found that the CP wave bandwidth for a 3 dB axial ratio criterion is twice as wide as that of the original antenna. Next, a spiral-type antenna is analyzed. It is revealed that the antenna shows a CP wave bandwidth of 28%, which is wider than that of the original antenna by a factor of 3.5. The analysis results are validated by experimental work.